Organizational learning improving learning, teaching, and leading in school systems - Collinson, Vivienne, 1949-; Cook, Tanya Fedoruk; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2006)
This innovative text about organisational learning in K-12 settings reshapes the way teachers and administrators think about people, practices, and policies while providing a compelling roadmap for transformation from within today's school systems.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: School management and organization; Educational leadership; Organizational learning; Electronic books